2021
DOI: 10.1080/10717544.2021.2015483
|View full text |Cite
|
Sign up to set email alerts
|

Carbopol emulgel loaded with ebastine for urticaria: development, characterization,in vitroandin vivoevaluation

Abstract: Urticaria affects all age groups of a population. It is triggered by allergens in foods, insect bites, medications, and environmental conditions. Urticaria is characterized by itching, a burning sensation, wheals and flares, erythema, and localized edema. The aim of this study was to develop a polymeric dosage form of ebastine using Carbopol 940 and mixture of span and tween. The emulsion was prepared, the gelling agent was added and the desired emulgel loaded with active drug was formulated. The formulations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Carbo had little effect on L929 fibroblasts in vitro. Because Carbo (Carbopol 980NF, Pharmacopeia/National Formulary) from Lubrizol Corporation is produced using a more toxicological preferred solvent such as a cosolvent mixture of ethyl acetate, it has been widely used in drug delivery and drug load due to its biosafety . Carbo could be a potentially biocompatible chelator in dentin adhesion in the future.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Carbo had little effect on L929 fibroblasts in vitro. Because Carbo (Carbopol 980NF, Pharmacopeia/National Formulary) from Lubrizol Corporation is produced using a more toxicological preferred solvent such as a cosolvent mixture of ethyl acetate, it has been widely used in drug delivery and drug load due to its biosafety . Carbo could be a potentially biocompatible chelator in dentin adhesion in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Because Carbo (Carbopol 980NF, Pharmacopeia/National Formulary) from Lubrizol Corporation is produced using a more toxicological preferred solvent such as a cosolvent mixture of ethyl acetate, it has been widely used in drug delivery and drug load due to its biosafety. 30 Carbo could be a potentially biocompatible chelator in dentin adhesion in the future. For in vivo evaluation, we designed a deep dentin defect model in rabbits to investigate the pulp response, when the etch-and-rinse adhesive system was applied.…”
Section: Biosafety Of the Novel Protocol Of Dentin Adhesionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown to be a good source of omega 3 PUFA, which act as modulators of cell signalling, gene expression, and inflammatory processes [ 15 ][ 16 ]. Because of its high cysteine and methionine content, it is widely known for its hydroxyl radical scavenging and anti-oxidant activities [ 16 , 17 ]. Previous study has demonstrated that flax seed possesses anti-oxidant and anti-microbial effects against gram-positive pathogens.…”
Section: Introductionmentioning
confidence: 99%